Thoracic endometriosis: a brief review - V., Dhruthi; Kondapuram, Veena; Datti, Sujata N.; Dalei , Bhubaneswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endometriosis is characterized by the presence of functional endometrial like glands and stroma outside the uterus. The most common extra pelvic site is thoracic cavity, which produces a range of clinical and radiological manifestations which include catamenial pneumothorax, hemothorax, hemoptysis, and pulmonary nodules resulting in thoracic endometriosis syndrome. This article reviews the condition of thoracic endometriosis syndrome, with details about symptoms, clinical examination, radiological features and management options are reviewed. The theories explaining such uncommon locations of endometriosis are discussed briefly. The role of local therapy and hormonal therapy, and description of our experience with two cases are presented.